2023
DOI: 10.2147/ijgm.s402683
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity in Newly Onset Diabetes Mellitus and Its Relationship with Uric Acid: An Indian Cross-Sectional Study

Abstract: Introduction Prevalence of obesity is high in diabetes mellitus (DM) and is associated with hyperuricemia (HU), hypertension, metabolic syndrome, cardiovascular disease and dyslipidemia. In obesity, elevated serum uric acid (SUA) has been shown to be associated in many studies from different countries, but data from India are lacking. The aim of the present study is to know the prevalence of obesity and to know the relationship between obesity and SUA in newly onset DM. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(63 reference statements)
0
1
1
Order By: Relevance
“…In 2023, a study conducted in India reported a mean BMI of 26.35±0.21 kg/m 2 in their newly onset diabetic patients with 141 participants being obese and 185 participants being overweight. 13 The population of males was greater than the females in our study reporting a ratio of 1:1. While the study in India reported a ratio of 0.96 with females being 51.11%.…”
Section: Discussioncontrasting
confidence: 51%
“…In 2023, a study conducted in India reported a mean BMI of 26.35±0.21 kg/m 2 in their newly onset diabetic patients with 141 participants being obese and 185 participants being overweight. 13 The population of males was greater than the females in our study reporting a ratio of 1:1. While the study in India reported a ratio of 0.96 with females being 51.11%.…”
Section: Discussioncontrasting
confidence: 51%
“…5 Hyperuricemia is associated with obesity, hypertension, diabetes, dyslipidemia, metabolic syndrome, liver dysfunction, cardiovascular disease, and chronic kidney disease as reported by several authors even if the mechanisms remain to be elucidated. [13][14][15][16][17][18][19] Given the appearance of cardiovascular and renal comorbidities after long exposure to hyperuricemia, it is difficult to know whether hyperuricemia is a risk mark for nongouty disease or factors associated with its. 2 Hyperuricemia constitutes a major public health issue due to its implication in many chronic diseases and metabolic syndromes.…”
Section: Introductionmentioning
confidence: 99%